Barriers of High Cataract Surgery Rate in Rural Area of Barisal Division (Journal of National Institute of Ophthalmology, 2023)
Background: Cataract is the leading cause of preventable blindness in the world. the most important component of vision 2020 to eliminate the cataract related blindness as a signatory of vision 2020 programme the government of Bangladesh takes many effective steps to increase cataract surgery rate CSR through national eye care operation plan but still there are some obstacles that desisted the rural people to undergo surgery for cataractAim of the study: To find out the reasons for the low cataract surgery rate among the cataract patients in rural area of Barisal division.Methodology: This cross-sectional study was conducted on the District Sadar Hospital, Jhalkathi from January 2016 to December 2016 over 200 patients out of 500 cataract patients who are selected for cataract surgery but did not under one the procedures finally not the medical ground. The causes of unwilling to undergo surgery was asked about by personal discussion through a structured questionnaire. All the relevant information was recorded in the data collection sheet and were analyzed and displayed for dissemination.Result: Out of 200 patients 91 patients did not undergo surgery due to fear about the surgical procedure, which followed by 43 patients who abstained from surgery due to fear of become total blind after surgery, 41 patients did not undergo surgery for not to bear the relevant expenditure the other reasons are no care giver for post-operative care and fear of complications (as experienced by persons, previously underwent surgery) which refrained 14 and 11 patients respectively from surgery.Conclusion: To increase the cataract surgery rate (CSR) in rural area among the under privileged people to achieve the goal of VISION 2020, it is necessary to conduct awareness program as well base hospitals should be equipped with effective instruments and skilled manpower.J.Natl.Inst.Ophthalmol.2023;6(1): 32-36